Sustavni prilaz problemu sigurnosti cestovnog prometa - Happ, Zdravko (Promet - Traffic&Transportation, 2012)
This paper discusses certain specific aspects and inevitable application of a system- oriented approach to the analysis of road traffic accidents as the basis for advanced analyst commitment. In the area of traffic accidents analysis an essential role is played by statistical processing of data. The accepted practice of statistical processing of RTA data compiled only by means of a Questionnaire cannot meet the requirements and expectations of an advanced analyst operation and commitment, mainly due to lesser reliability and deficiencies of the available data. Therefore the existing system of statistical data processing should be supplemented and advanced by processing of data from other more reliable sources of which the most important is related to the Road Traffic Accidents Data Bank created on the basis of expert verification of road traffic accidents.